2005
DOI: 10.1136/hrt.2004.054346
|View full text |Cite
|
Sign up to set email alerts
|

Collateral circulation in aortic coarctation shown by 64 channel multislice computed tomography angiography

Abstract: Objective: To determine whether ventricular arrhythmia related to nocturnal hypoxaemia during CheyneStokes respiration (CSR) explains the observation that CSR is an independent marker of death in heart failure. Design: Prospective, observational study. Patients: 101 patients at high risk of clinical serious ventricular arrhythmia fitted with an implantable cardioverter-defibrillator (ICD). Measurements: Patients were studied at baseline for CSR during sleep. Arrhythmia requiring device discharge was used as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 12 publications
1
6
0
1
Order By: Relevance
“…Moreover, the visualization of main vessels was very close to 100% and most undiagnosed images concerned secondary branch because of small size (second diagonal and second marginal vessels). The accuracy of MDCT in our populations was 91%, a value that is similar to previous studies with 16-row CT [7][8][9][10][11][12] and surprisingly better than in some of studies with 64-slice CT [13][14][15]. This may be explained by the fact that in most studies with 64-slice CT no segments were excluded, reducing the overall accuracy of the technique.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Moreover, the visualization of main vessels was very close to 100% and most undiagnosed images concerned secondary branch because of small size (second diagonal and second marginal vessels). The accuracy of MDCT in our populations was 91%, a value that is similar to previous studies with 16-row CT [7][8][9][10][11][12] and surprisingly better than in some of studies with 64-slice CT [13][14][15]. This may be explained by the fact that in most studies with 64-slice CT no segments were excluded, reducing the overall accuracy of the technique.…”
Section: Discussionsupporting
confidence: 87%
“…The introduction of 16-row and, more recently, 64-row scanners, provides promising results in the assessment of CAD [7][8][9][10][11][12][13][14][15]: these studies have shown high feasibility (from 84 to 100%), sensitivity (from 80 to 95%) and specificity (from 95 to 98%) but almost all of them are based on small cohorts of well-selected patients, and are based on the less clinically relevant segment model. To test the real clinical role, in our study we performed cardiac-CT in 144 consecutive nonselected patients referred to our hospital to perform a CA for suspected chest pain without previous history of significant CAD, excluding patients with absolute contraindications to MDCT (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients with less severe coarctation may not be diagnosed until later in childhood when a murmur is heard or hypertension noted. In these patients, collateral vessels develop from the internal thoracic and subclavian arteries, thyrocervical trunks, and vertebral and anterior spinal arteries to supply blood to the descending aorta [21,22] . For those who enter adulthood undiagnosed, hypertension is the most common presenting symptom [23] .…”
Section: Clinical Presentationmentioning
confidence: 99%